Living Hadits untuk Menciptakan Kehidupan Masyarakat Religius di Kelurahan Merjosari Kota Malang - Faruq, Muh.; Mustofa, Syaiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This paper aims to describe community service activities by seeking the realization of religious community life through the living hadith model, which is an effort that the hadith of the Prophet Muhammad SAW can be applied and integrated into people's lives. The target of this activity is the residents of Merjosari Village, Malang City, which is a densely populated urban area and is located close to several major educational institutions in Malang. This activity was carried out intensively using the service learning method by making the Raden Rahmat Merjosari Mosque as the basis of activities and the outcome of its activities was observed through direct observation and interviews. Through textual and contextual strategies in this living hadith model, it appears that there has been an increase and strengthening of the religious understanding of the people of Merjosari Village which can be seen from the strong belief of the community in God with the teachings of faith, the practice of praying in congregation in the mosque, inner experiences or expressions of serenity in life. , knowledge of religious teachings in the hadith, and the consequences in everyday life in the form of harmony and cohesiveness. This living hadith is also a provision for the community in realizing religious life so that they can respond to shifts in religious social values and are expected to reduce the potential for social conflicts that can occur at any time.